2016
DOI: 10.1542/hpeds.2015-0153
|View full text |Cite
|
Sign up to set email alerts
|

Emergency and Hospital Care for Food-Related Anaphylaxis in Children

Abstract: A B S T R A C TOBJECTIVES: Among patients with food-related anaphylaxis, to describe trends in emergency and hospital care and determine the revisit rate.METHODS: This retrospective cohort study included children 6 months to 18 years of age with food-related anaphylaxis from 37 children's hospitals between 2007 and 2012. Summary statistics and trends for patient characteristics were evaluated. Multivariable regression was used to identify predictors for hospital admission. Revisit rates to either the emergency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 16 publications
(16 reference statements)
2
35
0
Order By: Relevance
“…The major causative triggers of food-induced anaphylaxis in Qatar were nuts and eggs, a finding that was consistent with a Saudi finding reported in 2015 [14]. Peanuts, a major trigger of food-related anaphylaxis in the United States [7, 9, 22], is ranked in the fourth position after seafood in Qatar. In a prospective cohort study conducted in Qatar from 2007 to 2010, anaphylaxis induced by cow’s milk proteins (CMP) was found in 10 children out of 38 allergic subjects and suggested camel milk as a safer alternative choice after being experimentally tested [30, 31].…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The major causative triggers of food-induced anaphylaxis in Qatar were nuts and eggs, a finding that was consistent with a Saudi finding reported in 2015 [14]. Peanuts, a major trigger of food-related anaphylaxis in the United States [7, 9, 22], is ranked in the fourth position after seafood in Qatar. In a prospective cohort study conducted in Qatar from 2007 to 2010, anaphylaxis induced by cow’s milk proteins (CMP) was found in 10 children out of 38 allergic subjects and suggested camel milk as a safer alternative choice after being experimentally tested [30, 31].…”
Section: Discussionsupporting
confidence: 82%
“…In addition to potential differences in the genetic make-up, different life style and dietary patterns as well as differential prevalence of illnesses and use of varying medications may be some of the factors that may or may not contribute to such differences [18, 23]. In general, anaphylaxis was common [79, 20, 21], more associated with repeated use of epinephrine [27] and more fatal [23] among Caucasians compared to Black, Latino/Hispanic and Asian ethnicities. In contrast, Mahdavinia et al (2017) reported that Caucasians had a lower rate of food allergy associated anaphylaxis than African American and Hispanic children [37].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, as many as one fourth of those who experience an anaphylactic reaction in the school setting have no history of allergy . Among school children, food as a trigger for anaphylaxis has become a significant concern as the prevalence of food allergies continues to increase, as does the frequency of pediatric emergency department visits due to food‐induced anaphylaxis . It is now estimated that food allergies affect 1 in 20 school‐aged children, which translates to an average of at least 1 student per classroom…”
mentioning
confidence: 99%